'To see what's down there': Embodiment, Gestural Archaeologies and Materializing Futures. Issue 1 (March 2015) - Piccini, Angela
<x xml:space="preserve">Abstract</x> Concerns with screening embodiment have focused on the way in which cinema invites the spectator to consider a lived sense of the human body as a material subject that feels its own subjectivity. In this paper, I suspend the return of gesture to the transcendental human body. Gesture practises and produces complex and diverse bodies, bodies that do not precede their intra-actions but emerge through them. Drawing on the work of Karen Barad, I consider gesture in television that concerns archaeological practices in order to ask how gesture operates in this televisual subgenre to invite new ways of thinking about the human and other-than-human. Focusing on archaeology on television, I consider entangled gestures as intra-acting, material-discursive boundary-making practices that congeal and fix what we come to know as discrete, bounded bodies.